BiPO4 / CdIn2S4 composite photocatalyst, preparation method thereof and application of BiPO4 / CdIn2S4 composite photocatalyst in photocatalytic degradation of methylene blue

By constructing a composite photocatalyst with a BiPO4/CdIn2S4 heterojunction, the problems of fast recombination rate of photogenerated electron-hole pairs and low utilization of sunlight were solved, achieving efficient degradation of methylene blue. It has good stability and a simple preparation process, making it suitable for industrial applications.

CN121338779APending Publication Date: 2026-01-16NINGXIA UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511390617.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-26
Publication Date
2026-01-16

AI Technical Summary

Technical Problem

Existing photocatalysts have a fast photogenerated electron-hole recombination rate, resulting in insufficient generation of active species and low degradation efficiency; they also have low utilization of sunlight, narrow absorption range, and poor stability, making them difficult to apply industrially.

Method used

BiPO4/CdIn2S4 heterojunctions were constructed by mechanical mixing, with BiPO4 as a rod-like structure and CdIn2S4 as a micron-sized spherical structure assembled from nanosheets, in a molar ratio of 1:1 to 1:10. This method provides a simple composite photocatalyst that suppresses electron-hole recombination and broadens the light absorption range.

Benefits of technology

It significantly improves photocatalytic efficiency, achieving a methylene blue degradation rate of 99.31%, exhibits good stability, is suitable for industrial applications, and overcomes the shortcomings of traditional treatment methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121338779A_ABST
    Figure CN121338779A_ABST
Patent Text Reader

Abstract

The invention provides a BiPO4 / CdIn2S4 composite photocatalyst, a preparation method thereof and application of the BiPO4 / CdIn2S4 composite photocatalyst in photocatalytic degradation of methylene blue, and relates to the technical field of environmental catalytic materials.CdIn2S4 (indium cadmium sulfide) microspheres and rod-like BiPO4 (bismuth phosphate) are prepared through a hydrothermal method, and then a BiPO4 / CdIn2S4 heterojunction is constructed through a mechanical mixing method; wherein the optimal molar ratio of BiPO4 to CdIn2S4 is 1: 5 (marked as BC5). According to the composite photocatalyst disclosed by the invention, through the heterostructure design, the material contact area is obviously increased, the photo-induced electron migration path is shortened, the photo-induced electron-hole pair compounding is effectively inhibited, and the visible light absorption range is widened; under the optimal condition, the MB degradation rate within 180 min reaches 99.31%, the degradation rate is only reduced by 6.09% after five times of recycling, and the stability is excellent. The preparation process is simple and convenient, the cost is low, the methylene blue dye wastewater can be efficiently treated, and the industrial application prospect is wide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of environmental catalytic materials technology, specifically to BiPO4 / CdIn2S4 composite photocatalysts, their preparation methods, and their application in the photocatalytic degradation of methylene blue. Background Technology

[0002] There are over 700 commonly used dyes on the market, among which aromatic azo dyes (with methylene blue as a typical example) account for 50% of the total dye usage across various industries, making them the most frequently used. However, during dye production and dyeing processes, 5% to 15% of the raw materials are discharged with wastewater, forming toxic and carcinogenic polluted water bodies. Furthermore, aromatic azo dye molecules contain sp... 2 The hybrid azo and aryl structure is prone to DNA mutations, requires high chemical oxygen demand (COD) for degradation, leading to a sharp drop in dissolved oxygen in the water and the death of aquatic organisms, making degradation extremely difficult.

[0003] Current traditional methods for treating organic dye wastewater have significant drawbacks:

[0004] Adsorption method: It is easily affected by aerosols or impurities, which can lead to deactivation of the adsorbent;

[0005] Coagulation method: High operating cost, large amount of sludge and difficult dewatering, poor effect on hydrophilic dye treatment;

[0006] Microbial method: Microorganisms are sensitive to nutrients, pH and temperature, and have difficulty adapting to dyeing and printing wastewater with large fluctuations in water quality and high toxicity. In addition, the decolorization effect is poor and the COD removal rate is low.

[0007] Photocatalysis technology has become a research hotspot in the field of dye degradation due to its advantages of being environmentally friendly, economical, and highly efficient. Its principle is as follows: under sunlight irradiation, the photocatalyst generates electron-hole pairs (electron-hole pairs). - -h + ), e on the conductor band (CB) - It reacts with O2 to generate superoxide anion radicals (·O2). - This further generates hydrogen peroxide (H2O2) and hydroxyl radicals (·OH); ·O2 - ·OH is a highly oxidizing reactive oxygen species (ROS) that can mineralize organic pollutants into small molecule inorganic substances such as H2O and CO2.

[0008] However, existing photocatalysts have two major problems:

[0009] The high recombination rate of photogenerated electron-hole pairs leads to e - It cannot effectively participate in the degradation reaction, resulting in low photocatalytic efficiency.

[0010] It has low utilization of sunlight, absorbing only a portion of the spectral energy, which further weakens its degradation efficiency.

[0011] Therefore, developing a photocatalyst that can suppress electron-hole recombination, broaden the light absorption range, and is easy to prepare is of great significance for the treatment of methylene blue wastewater. Summary of the Invention

[0012] The excessively rapid recombination rate of photogenerated electron-hole pairs in existing photocatalysts leads to the deterioration of O2. - Insufficient generation of active species makes it difficult to efficiently advance the methylene blue degradation reaction;

[0013] Existing photocatalysts have low utilization rates of sunlight and narrow absorption ranges of visible light, which limit their degradation efficiency.

[0014] To address the problems of poor stability, complex preparation processes, and difficulty in industrial application of existing photocatalysts, this invention provides the following technical solution:

[0015] A BiPO4 / CdIn2S4 composite photocatalyst is formed by constructing a heterojunction from BiPO4 and CdIn2S4 through mechanical mixing. The BiPO4 has a rod-like structure, and the CdIn2S4 has a micron-sized spherical structure assembled from nanosheets with a diameter of about 6 μm. The molar ratio of BiPO4 to CdIn2S4 is 1:1 to 1:10.

[0016] As a further aspect of the present invention, the molar ratio of BiPO4 to CdIn2S4 is 1:5, denoted as BC5.

[0017] The preparation method of BiPO4 / CdIn2S4 composite photocatalyst includes the following steps:

[0018] Preparation of S1 and CdIn2S4: 1 mmol of cadmium chloride and 2 mmol of indium chloride were dissolved in 30 mL of deionized water, and 20 mL of deionized water containing 4 mmol of thiourea was added dropwise. After stirring for 1 h, the mixture was transferred to a 100 mL Teflon autoclave and hydrothermally treated at 180 °C for 18 h. The product was separated by centrifugation, washed alternately with deionized water and ethanol, and then vacuum dried at 80 °C overnight to obtain orange CdIn2S4 crystalline powder.

[0019] Preparation of S2 and BiPO4: 1.70 g Bi(NO3)3·5H2O was dissolved in 13.0 mL of 0.69 mol / L dilute nitric acid, denoted as solution A. 0.75 g (NH4)3PO4·3H2O was dissolved in 21.0 mL of deionized water, denoted as solution B. Solutions A and B were mixed and stirred for 1 h to obtain a white suspension. The suspension was transferred to a 50 mL Teflon-lined stainless steel reactor and hydrothermally treated at 200 °C for 20 h. After natural cooling to room temperature, rod-shaped BiPO4 was obtained.

[0020] Preparation of S3 and BiPO4 / CdIn2S4: BiPO4 and CdIn2S4 were added to 15 mL of deionized water by molar ratio, sonicated for 30 min, magnetically stirred at room temperature for 8 h, and centrifuged at 10000 r / min for 5 min. The precipitate was washed with deionized water and centrifuged 3 times, and then vacuum dried at 60 °C for 6 h to obtain the BiPO4 / CdIn2S4 composite photocatalyst.

[0021] As a further aspect of the present invention, the molar ratio of BiPO4 to CdIn2S4 in step S3 is 1:5.

[0022] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0023] The BiPO4 / CdIn2S4 composite photocatalyst and its application of the present invention have the following advantages:

[0024] Excellent performance: Through heterostructure design, photogenerated electron-hole pair recombination is suppressed (k value is increased by 6.81 times), the visible light absorption range is broadened, and the MB degradation rate reaches up to 99.31%.

[0025] Good stability: the degradation rate decreases by only 6.09% after 5 cycles, and it can be reused;

[0026] Simple preparation: It adopts a hydrothermal method + mechanical mixing method, which does not require high temperature treatment, and is simple to operate and low in cost;

[0027] High application value: It can efficiently treat methylene blue dye wastewater, overcome the shortcomings of traditional treatment methods, and has the potential for industrial application. Attached Figure Description

[0028] Figure 1 X-ray diffraction (XRD) patterns of BiPO4, CdIn2S4 and BiPO4 / CdIn2S4 composites;

[0029] Figure 2 (a) is a SEM image of CdIn2S4;

[0030] Figure 2 (b) is a SEM image of BiPO4;

[0031] Figure 2 (c) is the SEM image of BC5;

[0032] Figure 3 (a) shows the MB degradation curves for different catalysts; Figure 3 (b) is a first-order degradation kinetics curve; Figure 3 (c) is a histogram of dynamic constants; Figure 3(d) shows the cyclic degradation curve of BC5; Figure 4 (a) MB degradation curves at different BC5 dosages; Figure 4 (b) shows the first-order degradation kinetics curve; Figure 4 (c) is a histogram of dynamic constants; Figure 5 (a) shows the MB degradation curves at different pH values; Figure 5 (b) shows the first-order degradation kinetics curve; Figure 5 (c) is a bar chart of dynamic constants. Detailed Implementation

[0033] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.

[0034] Example 1

[0035] The preparation method of CdIn2S4 is as follows:

[0036] 1 mmol of cadmium chloride and 2 mmol of indium chloride were dissolved in 30 ml of water. 4 mmol of thiourea dissolved in 20 ml of water was added dropwise to this solution and stirred for 1 h. The resulting homogenized solution was transferred to a 100 ml Teflon autoclave and hydrothermally treated at 180 °C for 18 h. The product was centrifuged and washed several times with water and ethanol. Finally, the product was dried overnight in a vacuum oven at 80 °C to obtain orange CdIn2S4 crystalline powder.

[0037] The preparation method of BiPO4 is as follows:

[0038] 1.70 g of Bi(NO3)3·5H2O was dissolved in 13.0 mL of dilute nitric acid (0.69 mol / L) and magnetically stirred at room temperature (labeled as solution A). Then, 0.75 g of (NH4)3PO4·3H2O was dissolved in 21.0 mL of deionized water (labeled as solution B). Solution B was then mixed with solution A. After continuous stirring for 1 hour, a white suspension was obtained. This white suspension was then transferred to a 50.0 mL Teflon-lined stainless steel reactor and hydrothermally treated in an oven at 200 °C for 20 hours. After the oven cooled naturally to room temperature, BiPO4 was obtained.

[0039] The preparation method of BiPO4 / CdIn2S4 is as follows:

[0040] The prepared BiPO4 and CIS were mechanically mixed to form a BiPO4 / CdIn2S4 heterostructure. First, different molar ratios of BiPO4:CIS = 1:1, 1:5, and 1:10 (denoted as BC, BC5, and BC, respectively) were mixed. 10 The precipitate was added to three glass vials containing 15 mL of deionized water, sonicated for 30 min, magnetically stirred at room temperature for 8 h, and then centrifuged at 10000 r / min for 5 min. The resulting precipitate was washed with deionized water and centrifuged three times, and finally dried under vacuum at 60 °C for 6 h to obtain BiPO4 / CdIn2S4.

[0041] Experimental results

[0042] Structural and morphological characterization of BiPO4 / CdIn2S4 composite material:

[0043] First, the microcrystalline structure of the BiPO4 / CdIn2S4 composite material was analyzed by XRD. The observed diffraction peaks corresponded to the superposition of BiPO4 and CdIn2S4. Compared with the standard PDF cards of BiPO4 and CdIn2S4, there was no significant peak shift, which is because the mechanical mixing of these composite materials did not change the lattice structure of the material. Figure 1 The diffraction peaks of pure BiPO4 at 2θ = 18.6°, 19.0°, 24.2°, and 25.6° correspond to crystal planes (110), (011), (111), and (020), respectively. Furthermore, the diffraction peaks of pure CdIn2S4 at 2θ = 14.1°, 23.2°, 27.2°, 28.5°, 33.0°, 40.7°, 43.3°, 47.2°, and 55.2° correspond to crystal planes (111), (220), (311), (222), (400), (422), (511), (111), and (111), respectively. XRD results indicate that the composite material was successfully synthesized.

[0044] The morphology of the monomers and composite materials was observed using scanning electron microscopy (SEM). For example... Figure 2 As shown in (ac), CdIn2S4 is composed of nanoflowers assembled from nanosheets, with a size of about 6μm. BiPO4 is rod-shaped. In the composite BiPO4 / CdIn2S4, the rod-shaped BiPO4 is uniformly loaded on the micron-sized CdIn2S4 spheres, which greatly reduces the transfer path of photogenerated carriers, thereby accelerating the separation of photogenerated carriers and providing a larger contact area for more effective degradation of pollutants.

[0045] Performance of BiPO4 / CdIn2S4 composite material in degrading methylene blue:

[0046] The performance of the BiPO4 / CdIn2S4 photocatalyst was evaluated by using a 300W xenon lamp with a cutoff filter (λ≥420nm) as a visible light source to degrade methylene blue.

[0047] A 10 mg / L methylene blue simulated dye wastewater solution with a pH of 7.0 was prepared. 100 mL of this simulated wastewater was added to a 200 mL reactor. At room temperature, 30 mg of photocatalyst was used to degrade the methylene blue. The solution was stirred in the dark for 60 min to allow adsorption equilibrium. Then, the photocatalytic reaction was carried out for 3 hours under a 300 W xenon lamp and a 420 nm cutoff filter, with absorbance measured every 30 min. The remaining contaminants in the filtered methylene blue degradation solution were analyzed using a UV-Vis spectrophotometer (λ = 663 nm). (The sample was filtered using a 0.45 μm syringe filter before absorbance measurement).

[0048] In a preferred embodiment of the present invention, the degradation rate of the methylene blue is calculated using the following formula:

[0049] D(%)=[(C0-C t ) / C0]×100%

[0050] Where C0 is the initial concentration of methylene blue, C t This represents the concentration of methylene blue after degradation.

[0051] Next, to evaluate the photocatalytic activity of the BiPO4 / CdIn2S4 composite material, we added 30 mg of catalyst to 100 mL of 10 mg L-method. -1 In methylene blue solution, such as Figure 3 As shown in (a), after 60 minutes of adsorption equilibrium, there was no significant adsorption effect. After 180 minutes of visible light irradiation, BiPO4, CdIn2S4, BC, BC5, and BC... 10 The degradation rates of methylene blue were 20.92%, 54.61%, 60.8%, 95.12%, and 43.98%, respectively. BC5 showed the best photocatalytic degradation effect, which is because excessive BiPO4 would block the active sites on CdIn2S4, while insufficient BiPO4 would significantly weaken the separation of photogenerated carriers. Next, the degradation kinetics were studied, and a first-order degradation kinetic linear curve was obtained, as shown in... Figure 3 As shown in (b), the first-order kinetic line of BC5 has the largest slope, indicating that BC5 has the highest degradation efficiency. To more intuitively observe the slope change, a bar chart of kinetic constants was created, as shown below. Figure 3 (c) It can be seen that the kinetic constants of the composite catalyst are all larger than those of the two monomers. The largest kinetic constant for BC5 is 0.01293 min. -1 The values ​​were BiPO4 (0.0019 min) and BiPO4 (0.0019 min). -1 )and

[0052] CdIn2S4(0.0035min -1 The efficiency was 6.81 times and 3.69 times higher than that of BiPO4 and CdIn2S4, respectively. This demonstrates that the composite of BiPO4 and CdIn2S4 significantly improves photocatalytic efficiency. Furthermore, the stability of the composite material BC5 was also tested. Figure 3 (d) shows that after five cycles, the degradation rate of the BC5 composite material decreased by only 6.09%, indicating that BC5 has good stability.

[0053] The above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described herein. Although the present invention has been described in detail with reference to the above embodiments, the present invention is not limited to the specific embodiments described above. Therefore, any modifications or equivalent substitutions to the present invention, as well as all technical solutions and improvements that do not depart from the spirit and scope of the invention, are covered within the scope of the claims of the present invention.

Claims

1. A BiPO4 / CdIn2S4 composite photocatalyst, characterized in that: A heterojunction is formed by mechanical mixing of BiPO4 and CdIn2S4, wherein the BiPO4 is in a rod structure, the CdIn2S4 is in a micron-sized spherical structure assembled by nanosheets, the diameter is about 6 μm, and the molar ratio of BiPO4 to CdIn2S4 is 1:1-1:

10. 2.The BiPO4 / CdIn2S4 composite photocatalyst according to claim 1, characterized in that: The molar ratio of BiPO4 to CdIn2S4 is 1:5, and is denoted as BC5.

3. A method for preparing the BiPO4 / CdIn2S4 composite photocatalyst according to claim 1, characterized in that, The method comprises the following steps: S1, preparation of CdIn2S4: 1 mmol of cadmium chloride and 2 mmol of indium chloride are dissolved in 30 mL of deionized water, 4 mmol of thiocyanate is added dropwise in the form of a 20 mL deionized water solution, stirring is performed for 1 h, and then the mixture is transferred to a 100 mL Teflon autoclave, and hydrothermal treatment is performed at 180 ℃ for 18 h; the product is separated by centrifugation, washed with deionized water and ethanol alternately, and vacuum dried at 80 ℃ overnight to obtain orange CdIn2S4 crystalline powder; S2, preparation of BiPO4: 1.70 g of Bi(NO3)3·5H2O is dissolved in 13.0 mL of 0.69 mol / L dilute nitric acid, denoted as solution A, and 0.75 g of (NH4)3PO4·3H2O is dissolved in 21.0 mL of deionized water, denoted as solution B; solution A and solution B are mixed to obtain a white suspension, which is transferred to a 50 mL Teflon-lined stainless steel reactor, and hydrothermal treatment is performed at 200 ℃ for 20 h, and then the mixture is naturally cooled to room temperature to obtain rod-shaped BiPO4; S3, preparation of BiPO4 / CdIn2S4: BiPO4 and CdIn2S4 are added to 15 mL of deionized water in a molar ratio, ultrasonic treatment is performed for 30 min, and then magnetic stirring is performed at room temperature for 8 h, and then centrifugation is performed at 10000 r / min for 5 min; the precipitate is washed with deionized water and centrifuged for 3 times, and then vacuum drying is performed at 60 ℃ for 6 h to obtain a BiPO4 / CdIn2S4 composite photocatalyst.

4. The method of claim 3, wherein: In step S3, the molar ratio of BiPO4 to CdIn2S4 is 1:

5.

5. The use of the BiPO4 / CdIn2S4 composite photocatalyst according to claim 1 or 2, characterized in that: The method is used for photocatalytic degradation of an organic dye methylene blue.

6. Use according to claim 5, characterized in that: Specific conditions of the application include that the amount of the composite photocatalyst is 20-40 mg, the concentration of the methylene blue solution is 8-12 mg / L, the pH of the solution is 3-11, the light source is a 300 W xenon lamp (λ≥420 nm), and the solution is stirred in the dark for 60 min before photocatalysis.

7. Use according to claim 6, characterized in that: When the composite photocatalyst is BC5 (molar ratio of BiPO4 to CdIn2S4 is 1:1:5), the amount is 30 mg, the concentration of the methylene blue solution is 10 mg / L, the pH of the solution is 11, and the degradation rate of methylene blue is ≥99% after photocatalysis for 180 min.

8. Use according to any one of claims 5 to 7, characterized in that: After the composite photocatalyst is used for 5 times, the degradation rate of methylene blue decreases by ≤7%.